Analisis Wacana Terkait Percakapan Konsep Matematika - Herna Herna (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
This article offers discourse analysis to facilitate interpretation of discourse content presented in map form. This is intended to mean the content of discourse is not messy. Discourse analysis includes, selecting transcripts, creating lexical chain tables, constructing a "clean" map of semantic relationships between relevant content terms, semantic link analysis in transcripts, and building map transcripts using analysis from the previous stage.